2018
DOI: 10.1002/rmb2.12222
|View full text |Cite
|
Sign up to set email alerts
|

Advanced paternal age alone does not adversely affect pregnancy or live‐birth rates or sperm parameters following intrauterine insemination

Abstract: PurposeThis study aimed to evaluate the effect of advanced paternal age on pregnancy outcomes and sperm parameters following intrauterine insemination (IUI). We used IUI data rather than assisted reproductive technology data, which might mask the effects of sperm impairments.MethodsWe retrospectively analyzed 1576 IUI cycles in women under 40 years old between April 2012 and May 2016 at the National Center for Child Health and Development in Japan. The main outcomes were clinical pregnancy and live birth.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…Several recent studies have highlighted the difficulty in separating out APA from AMA. Tatsumi et al analyzed 1576 IUI cycles in women under 40 years old and that paternal age alone, after adjusting for confounding factors, was not associated with pregnancy or live birth rates [113]. The adverse effects of paternal age on IUI outcomes were mostly attributable to maternal age.…”
Section: Iui Outcomementioning
confidence: 99%
“…Several recent studies have highlighted the difficulty in separating out APA from AMA. Tatsumi et al analyzed 1576 IUI cycles in women under 40 years old and that paternal age alone, after adjusting for confounding factors, was not associated with pregnancy or live birth rates [113]. The adverse effects of paternal age on IUI outcomes were mostly attributable to maternal age.…”
Section: Iui Outcomementioning
confidence: 99%
“…It is commonly believed that the younger the woman, the higher the pregnancy rate, 7 and the age of the man is not associated with the pregnancy rate, with the age of the woman being the only factor affecting pregnancy. 8 In this study, the pregnancy rate gradually declined with age for women, but there was no significant decline in the pregnancy rate for men until 46 years of age. The ages of the married couples correlates with the pregnancy rate as shown in Fig.…”
Section: Discussionmentioning
confidence: 47%
“…In our study, unlike these studies, a statistically significant difference was found between pregnancy rates as sperm concentration increased. In a retrospective study including 1576 IUI cycles, it was reported that advanced male age had no effect on pregnancy (11). In our study, since there was no statistically significant difference between male and female ages between the two groups, it was not possible to investigate the effect of advanced male age on pregnancy.…”
Section: Discussionmentioning
confidence: 59%